RESPON SEMAI JABON MERAH (Anthocephalus macrophyllus (Roxb)) TERHADAP PEMBERIAN PUPUK ORGANIK LIMBAH KULIT BUAH KAKAO DITEMPAT PERSEMAIAN PERMANEN FATUKOA, NAIONI, KECAMATAN MAULAFA, KOTA KUPANG - NUSA TENGGARA TIMUR - Djara, Febi Tade; Pellondou, Mamie E.; Seran, Wilhelmina (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2022)
Red Jabon (Anthocephalus macrophyllus (Roxb)) is one of the forestry plants that has fast growing properties and is a native plant species of Indonesia. Jabon Merah plants need nutrients in their growth. This study aims to determine the response of red jabon seedlings (Anthocephalus macrophyllus (Roxb) to the application of organic fertilizer for cocoa pod waste. The research was conducted in Fatukoa permanent nursery from December 2020 to March 2021. The method used in this study was a completely randomized design method ( RAL) with one test with four treatments with five replications consisting of: M0 = Soil (4 kg), M1 = soil + organic fertilizer for cocoa pod waste (3 kg: 1 kg), M2 = soil + organic fertilizer for fruit peel waste cocoa (2 kg : 2 kg), M3 = soil + organic fertilizer cocoa pod waste (1 kg : 3 kg). Parameters observed were plant height (cm), stem diameter (mm), number of leaves (strands), seedling quality index, dry weight (total dry weight (gr), shoot dry weight (gr) and root dry weight (gr) ), seedling robustness (cm), shoot-to-root ratio (gr) and live percentage (%) of red jabon seedlings. The results showed that the application of organic fertilizer for cocoa pod waste had no significant effect on several parameters, including plant height, stem diameter (at 2MST, 8MST, 10MST and 12MST), number of leaves, seedling quality index (2MST and 4MST), root dry weight, seedling robustness (2MST, 6MST, 8MST, 10MST and 12MST), root shoot ratio and live percentage of red jabon seedlings, but had a significant effect on several observation parameters, namely stem diameter at 4MST and 6MST with an average range of 0.12- 0.29 and 0.29-0.65, seedling quality index at the age of 6MST, 8MST, 10MST and 12MST with a mean range of 0.0021-0.0097, 0.0024-0.0054, 0.0022-0.0120 and 0.0022-0.0122, total dry weight at age 12MST with a mean range of 0.0158-0.0871, shoot dry weight at age 12MST with an average range of 0.0147-0.0693, and seedling robustness at age 4MST with the mean range is 1.15-6.1257